Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3892/ijmm.2016.2673
|View full text |Cite
|
Sign up to set email alerts
|

TERT alleviates irradiation-induced late rectal injury by reducing hypoxia-induced ROS levels through the activation of NF-κB and autophagy

Abstract: The hypoxic microenvironment which is present following irradiation has been proven to promote radiation-induced injury to normal tissues. Previous studies have demonstrated that telomerase reverse transcriptase (TERT) is regulated by hypoxia, and that it plays a protective role in the process of wound repair. However, its effects on radiation-induced injury remain unclear. In this study, we examined the effects of human TERT on irradiation-induced late rectal injury in fibroblasts under hypoxic conditions. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…Next, we explored whether CAG had a protective role on TERT in primary human EpSCs. TERT, a reverse transcriptase of telomerase has been shown to be involved in certain types of injury through the activation of specific signals, such as NF-kappa B and autophagy [24], and it may have noncanonical functions in regulating the expression of particular genes [18]. As expected, in our real-time qPCR and western blot analysis, we found a significantly increased expression of TERT in EpSCs, which was related to improved proliferation and migration abilities.…”
Section: Discussionsupporting
confidence: 83%
“…Next, we explored whether CAG had a protective role on TERT in primary human EpSCs. TERT, a reverse transcriptase of telomerase has been shown to be involved in certain types of injury through the activation of specific signals, such as NF-kappa B and autophagy [24], and it may have noncanonical functions in regulating the expression of particular genes [18]. As expected, in our real-time qPCR and western blot analysis, we found a significantly increased expression of TERT in EpSCs, which was related to improved proliferation and migration abilities.…”
Section: Discussionsupporting
confidence: 83%
“…Hypoxia is a known inducer of autophagy (34). The present study demonstrated that the induction of autophagy and ROS production under hypoxic conditions, and autophagy inhibition by 3MA, led to a higher level of ROS production and cell apoptosis in R + and R − cells, which is in agreement with a previous study (35). …”
Section: Discussionsupporting
confidence: 94%
“…HO-1/BM-MSCs-treated group had the highest level of autophagy-related proteins LC3 II and Beclin-1, which suggested that significant amounts of autophagy occurred in the HO-1/BM-MSCs-treated group, and was consistent with ultrastructure results of the transplanted livers. Previous studies indicated that autophagy, as a cytoprotective mechanism, is involved in biological process such as growth, development and immune regulation ( 14 , 31 ). In addition, autophagy could relieve ischemia-reperfusion injury and induce immune tolerance in the organ transplantation ( 16 , 17 , 32 37 ).…”
Section: Discussionmentioning
confidence: 99%